2016
DOI: 10.1111/nph.13887
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of transcriptome sequences reveal multiple ancient large‐scale duplication events in the ancestor of Sphagnopsida (Bryophyta)

Abstract: SummaryThe goal of this research was to investigate whether there has been a whole-genome duplication (WGD) in the ancestry of Sphagnum (peatmoss) or the class Sphagnopsida, and to determine if the timing of any such duplication(s) and patterns of paralog retention could help explain the rapid radiation and current ecological dominance of peatmosses.RNA sequencing (RNA-seq) data were generated for nine taxa in Sphagnopsida (Bryophyta). Analyses of frequency plots for synonymous substitutions per synonymous sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 100 publications
2
40
0
Order By: Relevance
“…In addition, the orthology of these amino acid sequences was predicted through a BLASTP search against the nonredundant protein database and an OrthoMCL analysis (Li et al 2003). A BLASTCLUST search was conducted for paralog identification within each orchid species using the following parameters: e -value ≤10 −10 and 30% minimum similarity (–S 30) over 75% of the protein (–L 0.75) (Ponting and Russell 2002; Devos et al 2016). DIV - and RAD -like sequence information for O. italica , Ophrys , P. equestris , and D. catenatum is listed in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the orthology of these amino acid sequences was predicted through a BLASTP search against the nonredundant protein database and an OrthoMCL analysis (Li et al 2003). A BLASTCLUST search was conducted for paralog identification within each orchid species using the following parameters: e -value ≤10 −10 and 30% minimum similarity (–S 30) over 75% of the protein (–L 0.75) (Ponting and Russell 2002; Devos et al 2016). DIV - and RAD -like sequence information for O. italica , Ophrys , P. equestris , and D. catenatum is listed in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Among other plant groups, the moss Physcomitrella patens was also reported to have experienced a WGD (Rensing et al 2007), whereas multiple ancient WGDs were identified in the ancestor of the Bryophyta (Devos et al 2016). Our current understanding of genome or gene duplications in ferns comes from previous studies of chromosomal numbers and structure, synonymous substitution rates (Ks), and the transcriptomes of a few species (Barker 2009;Barker and Wolf 2010;Vanneste et al 2015;Clark et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The presence or absence of shared ‘age peaks’ in Ks plots of synonymous substitution rates between duplicates provides evidence for shared genome duplications [11]. This approach culminated in a survey of 41 plant genomes focusing on angiosperms [5] and more recently several transcriptomes also highlighting the presence of WGD within the evolutionary history of gymnosperms [12] and peat mosses [13]. The number and position of the peaks on the Ks plot also reveals the relative timing of each event, with multiple peaks representing multiple successive WGDs.…”
Section: Introductionmentioning
confidence: 99%